New omethid and lampyrid taxa from the Baltic Amber (Insecta: Coleoptera) - Kazantsev, Sergey V. (Zootaxa, 2012)
Two new fossil genera, Electromethes gen. n. (Omethidae) and Electotreta gen. n. (Lampyridae), and two new species,Electromethes alleni sp. n. and Electotreta rasnitsyni sp. n., are described from the Baltic amber. The new taxa appear to be related to the extant omethids (Electromethes) and ototretines (Electotreta) from the East Asia.